PENGGUNAAN AFIKS PADA BAHASA INDOGLISH DI GRUP GAME ONLINE HONKAI IMPACT 3 OFFICIAL INDONESIA - Damayanti, Ervina; Nurrahma, Avinta Ika; Siraj, Sultan Rafi Muhannad (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This research entitled The Use of Affixes on Indoglish Language in Online Game Group, Honkai Impact 3 Official Indonesia. This type of research is descriptive qualitatif. The object of this research is the form of language which is Indoglish. The source of the data in the research is the words Indoglish in the Honkai Impact 3 Official Indonesia online game buying and selling group on facebook. Data collection was carried out using note and listen comprehension techniques. The result of the study showed that there were affixations to various Indoglish languages in the official Indonesian Honkai Impact 3 Online game group, namely 1) prefixes nge-, ter-, ber-, di- , meng-2) suffixes –nya, -an, -kan 3) confixes (nge+kah) and (di+in).